Japan Government and NGOs Effort Towards Eliminating Racism in Japan - Angel Aurelia; Bero, Fransiska Priskilia; Santoso, Nethania Georgina Rosarika Surya (Department of International Relations, Brawijaya University, 2023)
Japan faced racist issues and it impacts the society. Which is crucial since society play an important role in a country. Therefore are there any efforts coming from the government of Japan and NGOs to solve this problem? Knowing the efforts made by both governments and NGOs to combat racism could help increase accountability, transparency, and public trust in these organizations and the initiatives they undertake. The primary data in this study were obtained from the results of interviews conducted by the authors of the informants, while the secondary data was in the form of documents and journals that were relevant and could support the research. The government does provide facilities such as consulting services for foreigners to report racist acts they experienced. The government and NGOs initiate a campaign in the form of a billboard. It is considered not effective and has little impact. On the other hand, the Japanese government has begun to socialize by giving some advice to companies in Japan to provide a Japanese language learning medium to train foreign workers. Based on the results of the research, most of our informants stated that the efforts made by the Japanese government and NGOs aren’t enough. The Japanese government and NGOs should consider bigger efforts to eliminate racism in their society. Keywords: Racism, Japan, Government, NGOs